John Patrick Reid , O. P., Anatomía del ateísmo, traducción de Néstor Ortiz Oderigo, Colección Esquemas, Editorial Columba, Buenos Aires; 1969, 65 pp. - Lértora Mendoza, Celina A. (1974)
Fil: Lértora Mendoza, Celina A. Investigador independiente